The passport database of VIR’s bean collection as a tool for systemizing bean genetic diversity, studying the collection’s history, and monitoring the crop’s worldwide breeding (an overview) - T. V. Buravtseva; G. P. Egorova; M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
The main document attesting the composition of a collection is the passport database (DB), which contains basic information about every accession: its name, status, origin, the year of its placement into the collection, etc. The effort to include every detail of such information into the database opens up a number of possibilities for structuring and exploring the diversity available. For the bean collection, the history of its systemization has had several stages. In 1923, systemic recording of bean accessions that entered the collection started with their registration in special journals, called catalogues. Since the middle of the 1960s, computer aids have been used for data logging and processing. In the 1990s, the DBs thus developed were transferred to personal computers. Today, such data are formatted as a computerized passport database, unified in accordance with modern international standards and consisting of 35 fields. Analysis of the Phaseolus passport database has shown that the bean collection consists of 6586 accessions, registered in the permanent catalogue. These accessions represent four cultivated species of different breeding status from 102 countries of the world. The largest percentage in the collection belongs to the accessions of European origin (61%). The accessions from North and South Americas (over 600 and 460 entries, respectively) make up 17% of the collection, while the gene pool of Asian countries, 16%. The biggest replenishments of VIR’s bean collection in its entire long history happened in the times of the USSR (2129 entries). The passport DB also makes it possible to conduct worldwide monitoring of the breeding work with beans, because it provides a comprehensive overview of the history of bean breeding and its present-day status in foreign countries, the ex-USSR republics and the Russian Federation. The purpose of this article has been to analyze the passport database of VIR’s bean collection and the information stored in it, and produce a retrospective essay on the documentation of the Phaseolus germplasm holdings at VIR.